Physiological Status of Stunned and Non-Stunned Broilers: Blood Profile, and Brain Histopathology (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2020)
Stunning method before slaughtering is considered more animal welfare compared to a non-stunning method and also reduces stress levels in broilers. As for the bleed-out efficiency, testing was done indirectly by blood volume measurement which consists of erythrocyte count, leucocyte count, hemoglobin levels, hematocrit values, and erythrocyte index in broilers.   Brain histopathology was also carried out to see the effect of electrical stunning towards the brain tissues.  The stunning method used is electrical stunning via water bath with the capacity of 146 mAh.  The results showed that the stunning method before slaughtering caused smaller number of erythrocytes and hematocrit values, and the brain histopathology showed that stunning causes encephalopathy.
Keywords: broilers; encephalopathy; slaughter; stunning